Fraudulent Financial Reporting Indications In Banking Before And During The COVID-19 Pandemic - Falsa Dzaky Arifian; Indira Januarti (Jurnal Akuntansi, 2023)
This study analyses indications of banking fraudulent financial reporting (FFR) before and during COVID-19. FFR indications are seen using the fraud pentagon theory through pressure (liquidity), opportunity (effective monitoring), rationalization (external auditor quality), competence (managerial ability), and arrogance (prominence of the CEO's photograph). This research was conducted on banks in the IDX from 2018 to 2021. The sample was selected using a purposive sampling method, consisting of 76 observations before COVID-19 (2018 to 2019) and 81 observations during COVID-19 (2020 to 2021). The analysis tool uses OLS regression. The results showed that rationalization negatively affects FFR indications before and during COVID-19, while competence had a positive effect only before COVID-19. The pressure, opportunity, and arrogance couldn’t indicate FFR before and during COVID-19. This research has implications for good auditor quality and managerial ability that can assist banks and regulators in building anti-fraud programs for preventing, detecting, and investigating FFR.